Effect of microorganisms on the fingerprint of the volatile compounds in pine nut (Pinuskoraiensis) peptide powder during storage. Issue 5 (1st April 2021) - Yang, Ruiwen; Lin, Songyi; Dong, Yifei; Ye, Haiqing; Zhang, Tiehua
Abstract: Pine nut (Pinus koraiensis ) peptide (PNP) powder possesses promising bioactivities. However, the powder may have the quality problem of becoming sticky and smelly. Therefore, the volatile compounds' fingerprint of PNP powder was established by headspace‐gas chromatography‐ion mobility spectrometry (HS‐GC‐IMS). The essential spoilage microorganisms were confirmed by 16S rDNA amplicon sequencing. The antioxidant activity, which presents PNP powder's quality, decreased during storage with the highest value of (1.88 ± 0.18) × 10 14 at day 30. Fifty‐nine significantly changed signals were detected; eight compounds were considered as volatile marker compounds. Besides, Firmicutes and Cyanobacteria were the essential spoilage microorganisms in PNP powder at the phylum level. Significantly, unidentified_Chloroplast, which belongs to Cyanobacteria, had a positive correlation with volatile marker compounds. The results proved that microorganisms indeed affect volatile compounds of PNP powder and induced off‐flavor, including hexanal, which can be used as the detection indicator for the quality control of PNP powder. Practical applications: In the present study, we controlled the influence of moisture migration on PNP powder and investigated microorganisms' effects on volatile compounds of PNP powder. HS‐GC‐IMS could be used to establish fingerprints of volatile compounds in PNP powder. 16S rDNA amplicon sequencing method could be used to screen the dominant spoilage bacteria in PNP powder and established essential spoilage microorganisms of PNP powder. This work provides a reference for category identification of PNP powder, which was infected by spoilage bacteria or not, and stored at day 0 or 30 days. Hexanal can be considered as the volatile marker compound generated from microorganisms. It helps to realize the controllability of PNP powder storage and prolongs the shelf life of PNP powder. Abstract : This work provides a reference for category identification of PNP powder, which was infected by spoilage bacteria or not, and stored at day 0 or 30 days. Hexanal can be considered as the volatile marker compounds generated from microorganisms. It helps to realize the controllability of PNP powder storage and prolongs the shelf life of PNP powder.